0555 The Relationship Between Sleep Efficiency and Apnoea Hypopnoea Index (AHI) in Adult Obese Males. (27th May 2020) - Ankita, A; Mehta, B; Dutt, N; Sharma, P
Abstract: Introduction: Prevalence of obesity is increasing worldwide. According to OECD 2017, the prevalence of obesity is 19.5% worldwide. Obesity leads to disturbed sleep due to complete or partial obstruction of upper airways i.e. obstructive sleep apnoea. This disturbed sleep leads to increased sympathetic discharge & further obesity and thus forms a vicious cycle of obesity disturbing sleep and sleep disturbance increasing obesity. The purpose of the present study was to correlate the sleep efficiency with apnoea hypopnea index (AHI) in adult obese males. Methods: Nineteen adult obese males (26 years- 60 years), non-smokers were recruited for this cross-sectional study. The obesity criteria was taken as BMI ≥ 25 kg/m 2 . They underwent an overnight polysomnographic examination with total 68 channels and 32 EEG inputs. The episodes of apnea were defined as complete cessation of airflow for ≥10 s, and hypopnea consisted of a ≥30% reduction in oronasal airflow accompanied by a reduction in oxygen saturation measured by pulse oximetry of at least 4%. AHI was determined by the frequency of these events per hour during sleep time based on the results of the overnight polysomnography. Sleep efficiency index was calculated by dividing total duration of sleep stages (N1+ N2+ N3+ REM) by total time in bed. Results: We tested for normality through Shapiro Wilk test and our data was found to be non-parametric. Hence Spearman correlation between sleep efficiency and AHI was performed. The correlation was non- significant with p value 0.1245 and r = - 0.365. The correlation of BMI with sleep efficiency was significant (p= 0.0195) with r value= -0.5303. Conclusion: The results conclude that the sleep efficiency worsens with obesity. Although the correlation between AHI and sleep efficiency was not found significant, a negative r value indicates that the sleep efficiency decreases with increased obstructive events during sleep. Support: All India Institute of Medical Sciences Jodhpur